Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.20944/preprints201608.0236.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Noise Pollution and Control in Wood Mechanical Processing Wood Industries

Abstract: High level of noise is a disturbance to the human environment. Noise in industries is also an occupational hazard because of its attendant effects on workers' health. Noise presents health and social problems in industrial operations, and the source is related to the machineries used in the industries. One of the unique features of the noise associated with wood machinery is the level of exposure and duration. Equipment used in a factory can be extremely loud. They can produce noise at decibels high enough to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 17 publications
3
11
0
2
Order By: Relevance
“…However, this study provides evidence that five Damietta wood factories and sawmills operate at or above the permissible exposure limit 90 dBA LAeq, which constitute a significant risk to the hearing of wood workers. These findings were in accordance with a study conducted in Nigeria indicated that 95 dB was the mean equivalent sound pressure level (LAeq) in the furniture industry [11] .…”
Section: Discussionsupporting
confidence: 92%
“…However, this study provides evidence that five Damietta wood factories and sawmills operate at or above the permissible exposure limit 90 dBA LAeq, which constitute a significant risk to the hearing of wood workers. These findings were in accordance with a study conducted in Nigeria indicated that 95 dB was the mean equivalent sound pressure level (LAeq) in the furniture industry [11] .…”
Section: Discussionsupporting
confidence: 92%
“…Pada saat proses memotong kayu, tingginya tingkat getaran pada blade disebabkan oleh serbuk kayu yang terperangkap di antara katrol dan blade. Getaran kayu yang digergaji merupakan sumber utama kebisingan (Owoyemi et al, 2017).…”
Section: Pembahasanunclassified
“…Burrowing is by living (Mollusca) marine craps and oyster (periwinkles). Detail works about the geology Niger delta exist in literature and can be found in (Ohwoghere-Asuma et al 2012;Rejier, 2011;Magbagbeoloa and Willis, 2007;Owoyemi andWillis, 2006, Ejedawe, 1981). Hydrogeology: The area is characterized by aquifers that are unconfined and confined.…”
Section: Ohwoghere-asuma Oghenero; Essi Oghenevovwero Emmanuelmentioning
confidence: 99%